Tiny Tools - Measuring Change in Communities and Groups - and Causemann, Bernward; Gohl, Eberhard; Brenner, Verena (Impact+, 2012)
Introduction to the Overview: Tiny Tools Why “Tiny Tools” for assessing change? Currently, change is mostly assessed by NGO staff or external experts. The vision of this paper is that communities assess and reflect change themselves and make use of that reflection with appropriate tools. All the tools presented here are relatively quick and easy to learn (therefore “tiny”). With Tiny Tools we can assess change in one session. They can therefore be used where there are not baselines. They are structured and systematic, and they are all widely tested: Experience shows that these tools lead to new insights, mobilise enthusiasm and increase the capacity of communities to bring about further change. The Tiny Tools are in line with what Participatory Rural Appraisal (PRA) wanted to achieve. Many are slight variations of PRA tools. For a detailed description of concepts, see the NGO-IDEAs Impact Toolbox (www.ngo-ideas.net/impact_toolbox) and the NGO-IDEAs Manual Self-Effectiveness (www.ngo-ideas.net/monitoring_self_effectiveness). The tools are designed to visualise change, but also enable communities to reflect on the reasons of change or verify assessments. They may be implemented once or continuously over time. We know that the time of community members is precious, and limited. Therefore all Tiny Tools can be performed in a relatively short session, provided facilitators (it could be field staff or project officers) are experienced – and the community knows and trusts them. The amount of time spent on the application of the tools may however be prolonged according to the needs of a community or NGO. All of these tools are easy to learn for a facilitator experienced in participatory processes. Which tool should be introduced to which community? It is typically the decision of a development organisation (or external experts) which tools they want to introduce into a community. The staff need to assess which tool will lead to learning and action. It could also be that the staff realise aspects of change that they do not understand well enough. These tools are good for exploring change that we have not planned for and not anticipated. They are also good for exploring change in a context where we have no prior information. Communities are the best experts for their situation, but we emphasise that the tools should be used in ways that benefit and empower the communities or individuals participating. The tool implementations should lead to consequences on the grassroots as well as the NGO level. All Tiny Tools can be integrated into PIAR, the Analysis tool in the NGO-IDEAs Impact Toolbox. Also, the Tiny Tools can help to prepare for the application of the Toolbox tools. They help to make people aware of changes that can be observed. The following box gives some hints how Tiny Tools relate to the Impact Toolbox tools, and to what extent they help to attribute change to development interventions.